2011
DOI: 10.1186/1749-8090-6-20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ankaferd Blood Stopper on air leakage in the lung and prevention of bleeding: an experimental study

Abstract: BackgroundAir leakage and hemorrhage are important causes of morbidity and mortality in operations and traumas of the lung. Ankaferd Blood Stopper is a herbal product used for stopping hemorrhage. In our study, we investigated the efficacy of Ankaferd Blood Stopper in the prevention of air leakage in the lung and bleeding.MethodsA total of twenty-one Wistar-Albino rats weighing 240 ± 20 grams were used in our study. An equal amount of injury was created in all groups by performing left thoracotomies. No interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Using an animal model, Kose et al demonstrated that ABS is a potent hemostatic agent for cutaneous bleeding resulting from surgical skin defects (13). The effects of ABS in preventing liver lacerations, partial nephrectomies, air leakage into the lung, and bleeding have been demonstrated via animal studies (14)(15)(16)(17). In another animal study, İşler et al reported that ABS causes new bone formation and reductions in necrosis and inflammation in a rat tibial defect model (18).…”
Section: Discussionmentioning
confidence: 98%
“…Using an animal model, Kose et al demonstrated that ABS is a potent hemostatic agent for cutaneous bleeding resulting from surgical skin defects (13). The effects of ABS in preventing liver lacerations, partial nephrectomies, air leakage into the lung, and bleeding have been demonstrated via animal studies (14)(15)(16)(17). In another animal study, İşler et al reported that ABS causes new bone formation and reductions in necrosis and inflammation in a rat tibial defect model (18).…”
Section: Discussionmentioning
confidence: 98%
“…Kılıçgün et al (13) investigated the efficacy of ABS in the prevention of air leakage in the lungs and bleeding in an animal experiment. The results showed that ABS terminated air leakage in the lung parenchyma significantly and effectively.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] The hemostatic effects of ABS have been demonstrated by in vitro and in vivo studies in the Literature. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] The topical application of ABS as a hemostatic agent in the external hemorrhages and during dental interventions constituted the first hints about the safety and efficacy of ABS in humans. 13 A recent in vitro study suggested that topical application of ABS to ocular surfaces could affect cellular constituents.…”
mentioning
confidence: 99%